KEBAN BARAJ GÖLÜ AYNALI SAZANLARININ (CYPRİNUS CARPİO L.) MİKROBİYOLOJİK, KİMYASAL KALİTESİ VE ET VERİMİ - ARSLAN, ALİ (Fırat Üniveristesi, 1992)
The purpose of tiie study was to determine the chemical and microbiological quality and the meat yield of mirror carp (Ccarpio L.) caught in Keban Dam Lake. 64 fishes were used for microbiological analysis while 26 male anda 28 female fishes (total : 56 fishes) were analysed for determining the chemical quality and meat yield. Tests were repeated twice a month for 12 months. The annual average numbers of microorganisms determined in tne skin and in the meat of mirror carp were as follows : Skin Meat Viable aerobes 1.8 x 10-Vgr 5.0 s 102 /gr Conforms 11 xlO^/gr None Faecal streptococcus 1.3 x 10^ /gr None Yeast and Molds 8.6xiû^/gr None Proteolytics 1.2 s 104/gr 2.3 x 10l/gr Staphylococcus 6.4 x 10-Vgr 0.6 xioVgr Viable aerobes and Staphylococcus in skin reached to the maximum number in spring; Faecal streptococcus in summer; conforms, proteolytics, yeasts and molds in winter. Viable aerobes in meat reached to the maximum number (.3.6 x 10-tygr) in spring. Average values for chemical analysis were as follows : Male Female 78.99 17.83 2.20 0.9569 Ö2E£ Bu çalışma, Keban baraj gölü aynalı sazanlarının (C.carpio L.) mikrobiyolojik, kimyasal kalitesi ve et verimini saptamak amacıyla yapıldı. Araştırmada mikrobiyolojik analizler için 64 adet, kimyasal kalite ve et verimini saptamak için işe 26 erkek ve 26 dişi olmak üzere toplam 56 balık incelendi. Deneyler ayda iki defa olmak üzere 12 ay sûreyle tekrarlandı. Deri ve kastan saptanan ortalama mikroorganizma sayısı: Deri Kaş l.dziO-Vgr 5.2xlOVgr Genel koli, İJ x lO"Vgr üremedi Fecal streptococcus 1.3 x 10-* /gr üremedi Maya -küf S.bxlOVgr üremedi Proteolitik 1.2 x 104/gr 0.6 x 10 i /gr Staphylococcus 6.4 x 10 * /gr 2.3 x lOVgr IkroUeİlkbaharda genel aerop, Staphylococcus; yazın Fecal streptococcus; kısın genel koli, maya-kûf ve proteolitik mikroorganizmalar en yüksek sayıya utasü. Kasta, genel aerop sayısı ilkbaharda en yüksek sayıda (3.6 x 10^/gr) tespit edildi. Erkek ve dişi aynalı sazanların ortalama kimyasal kompozisyonu: er* 9. Erkek balıklarda, protein ve kül ilkbaharda; rutubet sonbaharda;

Bu çalışma, Keban baraj gölü aynalı sazanlarının (C.carpio L.) mikrobiyolojik, kimyasal kalitesi ve et verimini saptamak amacıyla yapıldı. Araştırmada mikrobiyolojik analizler için 64 adet, kimyasal kalite ve et verimini saptamak için işe 26 erkek ve 26 dişi olmak üzere toplam 56 balık incelendi. Deneyler ayda iki defa olmak üzere 12 ay sûreyle tekrarlandı. Deri ve kastan saptanan ortalama mikroorganizma sayısı: Deri Kaş l.dziO-Vgr 5.2xlOVgr Genel koli, İJ x lO"Vgr üremedi Fecal streptococcus 1.3 x 10-* /gr üremedi Maya -küf S.bxlOVgr üremedi Proteolitik 1.2 x 104/gr 0.6 x 10 i /gr Staphylococcus 6.4 x 10 * /gr 2.3 x lOVgr IkroUeİlkbaharda genel aerop, Staphylococcus; yazın Fecal streptococcus; kısın genel koli, maya-kûf ve proteolitik mikroorganizmalar en yüksek sayıya utasü. Kasta, genel aerop sayısı ilkbaharda en yüksek sayıda (3.6 x 10^/gr) tespit edildi. Erkek ve dişi aynalı sazanların ortalama kimyasal kompozisyonu: er* 9. Erkek balıklarda, protein ve kül ilkbaharda; rutubet sonbaharda;72 Protein and ash in male fishes reached to üıeir maximum values in spring, moisture in autumn and fat in winter. In females moisture had its maximum value in autumn, protein and fat in summer and ash in spring. There was no statistical differences among sexes for moisture, protein and ash while fat was found to be higher in males than females. The average meat yield in males fishes was % 52.10 and reached to its maximum in summer as % 54.07. In females, the average meat yield was % 51-69 and its - maximum was % 54.46 in autumn. The effect of sex on meat yield was not important There was a positif correlation (P<0.01}inmateand female fishes for annual average values between the meat yield and total weight, head, skin, fin, fin ray, internal organs, fishbone, blood and moisture. Meat and scale values did not have any correlation. It was conculudet that the microbiological and chemical quality and yield of mirror carp caught in Keban Danı Lake were comparably sood.
Keywords: Veteriner Hekimliği; Veterinary Medicine